1961
DOI: 10.1177/004051756103100209
|View full text |Cite
|
Sign up to set email alerts
|

Some Theoretical Considerations of Cellulose Cross-Linking

Abstract: Much available chemical evidence supports the hypothesis that covalent cross-linking is the best way to improve the resilience of cellulosic fabrics. This paper reviews the theories relating physical properties to cross-linking in rubbery polymers and shows that they apply in some qualitative aspects to cellulose. Particularly, the observed changes in swelling, solubility, modulus, tensile strength, and resilience are consistent with these theories.On the basis of published data, the concentration of intermole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1961
1961
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Th e introduction of covalent cross-links into cellulosic fi bres has two important eff ects, i.e. i) it reduces the mobility of chain molecules to move laterally [10], and ii) it extends longitudinally under stress [10,11]. Studies have shown that the unavoidable side eff ect of cross-linking fi nishes is a reduction in elasticity and fl exibility of cellulosic fi bres, next to a considerable decrease in abrasion resistance, tear and tensile strength [12].…”
Section: Izvlečekmentioning
confidence: 99%
“…Th e introduction of covalent cross-links into cellulosic fi bres has two important eff ects, i.e. i) it reduces the mobility of chain molecules to move laterally [10], and ii) it extends longitudinally under stress [10,11]. Studies have shown that the unavoidable side eff ect of cross-linking fi nishes is a reduction in elasticity and fl exibility of cellulosic fi bres, next to a considerable decrease in abrasion resistance, tear and tensile strength [12].…”
Section: Izvlečekmentioning
confidence: 99%
“…tions may also have increased in length. Gardon and Steele [7] ] have discussed the loss in strength of cotton with application of a crosslinking agent in terms of the effect of crosslinking on the strength of rubberlike polymers. In light of the very high crystallinity cotton is now thought to have, it would appear to be difficult to draw too many analogies between rubber and cotton cellulose.…”
Section: Figure 2 )mentioning
confidence: 99%
“…It is possible, then, that cotton in the mercerized state can be considered to be equivalent to a highly crosslinked rubber [ 7 ] . The relation between the strength of rubberlike polymers and the degree of crosslinking passes through a maximum as crosslinking is increased.…”
Section: Figure 2 )mentioning
confidence: 99%
“…Several different methods have been used to measure the friction (see bibliography given by Moncrieff [12] and see also Flanagan [6], Lyons [9J, Scheier and Lyons [14 ). The capstan method, in which the wool fiber is drawn round a rod of some suitable material, has been and appears likely to remain the most popular, not because it is the best suited to the study of the role of single-fiber friction in any particular set of circumstances, but because it is so easy to use.…”
Section: Introductionmentioning
confidence: 99%